Zinc Removal from Industrial Wastewater by Electro-Coagulation Process - K. Shakir, Ibtehal; S. Sabeeh, Nawras (Iraqi Journal of Chemical and Petroleum Engineering, 2007)
Electro coagulation treatment was used for zinc removal from electroplating wastewater of the State Company for Electrical Industries . This wastewater, here consists zinc ions with maximum concentration in solution of 90 ppm .The parameters that influenced the wastewater treatment are: current density in the range  1-1.4 mA/cm2, pH  in the range 5-10, temperature in the range 25-45°C and time in the range 10-180 minute.The research is a laboratory experimental type using batch system for electrical process with direct current. The cell comprised of aluminum electrode as anode and stainless steel electrode as cathode. Thirty experiments and one hundred fifty sample lab tests were carried out in this research to study the effect of the mentioned parameters on the efficiency of the removal process .Experimental work of this research proved a higher efficiency about 95 % removal of zinc from wastewater at 1. 4 mA/cm2, in alkaline media at pH equal 10 and temperature 45°C.